Mango Leaf Webber (Orthaga euadrusalis Walker, (Pyralidae: Lepidoptera); A Potential Threat in Tropical Plains of Nepal - Shrestha, Saroj; Chaudhary, Manisha; Upadhyaya, Navaraj; Khanal, Dipak (Nepalese Horticulture, 2022)
Mango Leaf Webber (Orthaga euadrusalis Walker, 1858) is a phytophagous insect feeding on mango leaves by scraping the leaf surface leaving behind midribs and habitat inside the webbed leaf bunch, which is one of the major pests of mango in south Asian nations including Nepal. The infestation of the pest has the potential to cause production loss of 25-100% if not managed. Thus, the management of the pest is crucial to protect mango production and collateral economics. For management, the web nest can be scraped off and burnt along with pupa and larva. Integrated management practices include biological methods using predators like Brachymeria lasus, Hormius, Hormiusa, Pediobius bruchicida, Oecama sp., etc. pathogens like Serratia marcescens and Beauveria bassiana, etc., pruning and removal of old and infested branches and planting resistant variety like Amrapali, the legal method by regulating mobility of plant parts as well as the chemical method by using chemical pesticides like Quinalphos, Cypermethrin, Chlorpyriphos, Acephate and botanical pesticides like Nimbicidine, Nemactine, etc. for management of the pest. The management methods given in this paper would be a valuable resource for mango growers, researchers, and consumers in managing the mango leaf Webber problem.